(untitled) (CIPEEX, 2025)
The objective of this study was to identify the structural characteristics for the Digital Transformation (DT) of health in Brazil. A structured bibliographic search was chosen, conducted in five stages. It was perceived that DT involves a multidisciplinary change, which impacts how companies do marketing, distribute services, and use information technology, forcing a reassessment of organizational strategies to ensure sustainability and competitiveness in the market. In the health sector, DT follows a path similar to other sectors, absorbing the capacity to innovate in the provision of services and improve user participation. DT is divided into three main phases that have significant impacts, such as reducing operational costs and creating smart companies, but also present challenges, such as the need to develop new organizational cultures and digital skills. It is concluded that Brazil, particularly in the Health Sector, has been following the global digital transformation. The proposal for Digital Health in the country represents innovation by providing platforms that facilitate patient participation in the healthcare provision process, through the encouragement of digital technology use.